USAHA KEGIATAN MASYARAKAT PENGERING IKAN DI KECAMATAN PITUMPANUA-SIWA KAB. WAJO SULAWESI SELATAN - Lendri, Lendri; Husniati, Husniati (Jurnal BALIRESO, 2018)
Priority issues for both partners are; (1) Production problem; dirty water source used and badquality of raw material of dried fish Becouse drying method used was conventional method, sothat the volume and quality of dried fish produced are very low and, (2). Management problem;lack of knowledge of financial bookkeeping management and bad marketing strategy. Offeredsolution to the partners was the use of fish drying machine as one of the effective, efficient costeffectivemethods of higienes drying fish during the rainy season. Output of IbMs activities wasthe use of low-voltage gas and electric of fish dryers. According to the partners, profit obtainedafter IbM activities was able to produce dried fish up to 50% of normal production. Although theprice of dry fish rose by 10% only during the rainy season, but with the dryer, the partner stillearns a maximum profit of 5% rom normal sales.